Interaction of ruminant transferrins with transferrin receptors in bovine isolates of Pasteurella haemolytica and Haemophilus somnus. - Yu, R H (1992)
The interactions of ruminant transferrins with receptors on bovine isolates of Pasteurella haemolytica and Haemophilus somnus were compared by growth studies and direct and competitive binding assays. Isolates of P. haemolytica were capable of utilizing and binding transferrin from sheep, goat, or cattle, whereas isolates of H. somnus were capable of utilizing and binding only bovine transferrin.